Methods for Complexing Images Formed by Multi-Band Synthetic Aperture Radars - A. A. Potapov; V. A. Kuznetsov; E. A. Alikulov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Synthetic aperture radars (SAR) are important components of aviation-based systems for remote sensing of the Earth. The current level of such systems allows simultaneous radar surveys in several frequency ranges. Such surveys require complexing of the images formed in each of the frequency channels, which task is yet to be resolved.Aim. To review the formation principles and methods for joint processing of images using space and aviation-based multi-band synthetic aperture radar systems.Materials and methods. The methodology of systems analysis, involving the integral stages of decomposition, analysis and synthesis, was used. Decomposition of integrating multi-band radar images was performed considering the effect of various factors on the characteristics of radar images in different frequency ranges. Such factors include the principles of radar imaging, issues of radar images of multi-band synthetic aperture radars with real characteristics, and complexing levels.Results. According to the classical systems approach, the results of review and analysis are corresponded by appropriate conclusions on the shortcomings of each decomposition element and the synthesis of a proposal for achieving the goal. It was shown that joint processing of multi-band radar images can be carried out at the levels of signals, pixels, features and solutions, as well as their aggregates. Each approach is characterised by its shortcomings, which impede implementation of full integration of multi-band radar images without loss of information, which is due to the absence of information redundancy of radar images, compared to, e.g., optical images.Conclusion. Recommendations on the application of a particular method and the synthesis of a system for radar complexing images based on the texture-fractal approach were formulated. Directions for further work meeting all the requirements for completeness, reliability and information content of remote sensing of the Earth were outlined.